Inovasi Bahan Ajar Pragmatik Berbasis Kearifan Lokal dengan Metode Permainan Bahasa (Language Game) di Madrasah Ibtidaiyah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This research is motivated by the low pragmatic competence of Madrasah Ibtidaiyah (MI) students, which is shown by the high rate of pragmatic failure (65%) and learning participation (40%), as well as the lack of contextual teaching materials. The purpose of the research is to identify learning barriers, then design, and test the initial impact of pragmatic teaching material innovation based on local wisdom through language play methods. With the Design-Based Research (DBR) approach involving teachers and students of MI in Central Java, data was collected through interviews, observations, and document studies, and then analyzed thematically. The results of the study revealed three main obstacles: (1) non-contextual teaching materials, (2) limited methodological skills of teachers, and (3) low student motivation. As a solution, "PRAGAMALOKA" teaching materials were developed that transform the values of local wisdom (tepo seliro, gotong royong) and traditional games (dakon) into the core of pragmatic learning scenarios. The limited trial showed a significant increase in student engagement and positive response. This study concludes that substantive integration between local content, pragmatic goals, and play methods is the key to creating authentic and meaningful learning. Implicitly, this development model can be adopted to design other contextual teaching materials, with recommendations for further experimental tests to measure their comparative effectiveness.